Detection and Grading of Gliomas Using a Novel Two-Phase Machine Learning Method Based on MRI Images - Chen, Tao; Xiao, Feng; Yu, Zunpeng; Yuan, Mengxue; Xu, Haibo; Lu, Long (Frontiers in Neuroscience, 2021)
The early detection and grading of gliomas is important for treatment decision and assessment of prognosis. Over the last decade numerous automated computer analysis tools have been proposed, which can potentially lead to more reliable and reproducible brain tumor diagnostic procedures. In this paper, we used the gradient-based features extracted from structural MRI images to depict the subtle changes within brains of patients with gliomas. Based on the gradient features, we proposed a novel two-phase classification framework for detection and grading of gliomas. In the first phase, the probability of each local feature being related to different types (e.g., diseased or healthy for detection, benign or malignant for grading) was calculated. Then the high-level feature representing the whole MRI image was generated by concatenating the membership probability of each local feature. In the second phase, the supervised classification algorithm was used to train a classifier based on the high-level features and patient labels of the training subjects. We applied this framework on the brain imaging data collected from ZhongNan Hospital of Wuhan University for glioma detection, and the public TCIA datasets including glioblastomas (WHO IV) and lower grade gliomas (WHO II and III) data for glioma grading. The experimental results showed that the gradient-based classification framework could be a promising tool for automatic diagnosis of brain tumors.